Shark‐dust: Application of high‐throughput DNA sequencing of processing residues for trade monitoring of threatened sharks and rays - Andhika P. Prasetyo; Joanna M. Murray; Muh. Firdaus A. K. Kurniawan; Naiara G. Sales; Allan D. McDevitt; Stefano Mariani (Conservation Letters, 2023)
Abstract Illegal fishing, unregulated bycatch, and market demand for certain products (e.g., fins) are largely responsible for the rapid global decline of shark and ray populations. Controlling trade of endangered species remains difficult due to product variety, taxonomic ambiguity, and trade complexity. The genetic tools traditionally used to identify traded species typically target individual tissue samples, and are time‐consuming and/or species‐specific. Here, we performed high‐throughput sequencing of trace DNA fragments retrieved from dust and scraps left behind by trade activities. We metabarcoded “shark‐dust” samples from seven processing plants in the world's biggest shark landing site (Java, Indonesia), and identified 61 shark and ray taxa (representing half of all chondrichthyan orders), more than half of which could not be recovered from tissue samples collected in parallel from the same sites. Importantly, over 80% of shark‐dust sequences were found to belong to CITES‐listed species. We argue that this approach is likely to become a powerful and cost‐effective monitoring tool wherever wildlife is traded.